Polish Tax Cases before the European Court of Human Rights - Baker, Philip (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
This chapter considers the cases that have been decided by the European Court of Human Rights emanating from Poland. By “tax cases” a broad approach is taken, and any cases that have tax issues at their core are regarded as falling within this classification. Thus, as will be seen, one of the cases discussed concerns the freedom of expression of journalists writing about the motivation behind changes in tax law.